(untitled) (Journal of Event, Tourism and Hospitality Studies, 2025)
This study explores the influence of motivation and satisfaction on visitor loyalty in the context of adventure tourism, focusing on the Skywalk activity at Kuantan 188 (K188) Tower in Kuantan Pahang, Malaysia. As experience-driven travel becomes increasingly prominent, understanding the psychological and experiential factors that encourage visitor retention is essential for sustainable tourism development. Employing a quantitative research design, data were collected from 265 visitors using purposive sampling, targeting individuals who had experienced the skywalk activity. A structured questionnaire measured motivation, satisfaction, and loyalty using a 7-point Likert scale, and the instrument demonstrated high reliability across constructs (Cronbach’s α >0.90). The data were analyzed using descriptive statistics and multiple regression analysis to examine the relationships among the variables. The findings reveal that both motivation (β = 0.320, p < .001) and satisfaction (β = 0.531, p < .001) significantly influenced visitor loyalty, with satisfaction emerging as the stronger predictor. These results underscore the importance of delivering fulfilling and emotionally engaging experiences in enhancing loyalty especially in exciting and thrilling adventure tourism and nature-based tourism environments. The study contributes to the growing body of adventure tourism literature by empirically validating the link between visitor experience components and loyalty behavior. The findings offer valuable insights for tourism managers, marketers, and policymakers in designing targeted, experience-based tourism strategies.